Hyaluronic acid/polyethyleneimine nanoparticles loaded with copper ion and disulfiram for esophageal cancer. (1st June 2021) - Xu, Ru; Zhang, Kun; Liang, Jiaheng; Gao, Feng; Li, Jingan; Guan, Fangxia
Highlights: Disulfiram combined with Cu 2+ shows excellent curative effect for cancer patient. The HA/PEI nanoparticles are designed as carriers for the disulfiram and Cu 2+ . The HA/PEI nanoparticles loaded disulfiram/Cu 2+ present stronger Targeting and effectiveness. The HA/PEI nanoparticles loaded disulfiram/Cu 2+ are anticipated to make better contribution to cancer treatment. Abstract: In the clinical treatment of cancer, improving the effectiveness and targeting of drugs has always been a bottleneck problem that needs to be solved. In this contribution, inspired by the targeted inhibition on cancer from combination application of disulfiram and divalent copper ion (Cu 2+ ), we optimized the concentration of disulfiram and Cu 2+ ion for inhibiting esophageal cancer cells, and loaded them in hyaluronic acid (HA)/polyethyleneimine (PEI) nanoparticles with specific scales, in order to improve the effectiveness and targeting of drugs. The in vitro cell experiments demonstrated that more drug loaded HA/PEI nanoparticles accumulated to the esophageal squamous cell carcinoma (Eca109) and promoted higher apoptosis ratio of Eca109. Both in vitro and in vivo biological assessment verified that the disulfiram/Cu 2+ loaded HA/PEI nanoparticles promoted the apoptosis of cancer cells and inhibited the tumor proliferation, but had no toxicity on other normal organs.